2015
DOI: 10.2147/ppa.s87069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the characteristics and prognosis of advanced non-small-cell lung cancer in older patients

Abstract: ObjectiveLung cancer is still the leading cause of cancer-related deaths worldwide. However, most elderly patients with advanced non-small-cell lung cancer (NSCLC) have been undertreated and the outcome related to age is controversial. A retrospective analysis was conducted for advanced NSCLC in order to investigate the characteristics and prognosis of older patients.MethodsMedical records were collected from 165 patients with NSCLC (stages IIIA–IIIB) who had been treated with concurrent chemoradiotherapy (CRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The mutational landscape present in a cancer genome is the cumulative result of endogenous and/or exogenous mutational processes (e.g., smoking), constant or sporadic and with different strengths along patient ageing [ 4 7 ]. Therefore, multiple mutational processes are operative resulting in jumbled composite signatures and tumor characteristics vary between patients of different ages [ 7 9 ]. From the Catalogue Of Somatic Mutations In Cancer (COSMIC) which includes 10,952 exomes and 1,048 whole-genomes across 40 distinct types of human cancer [ 10 ], 30 different mutational signatures were identified and publicly released ( http://cancer.sanger.ac.uk/cosmic/signatures ).…”
Section: Introductionmentioning
confidence: 99%
“…The mutational landscape present in a cancer genome is the cumulative result of endogenous and/or exogenous mutational processes (e.g., smoking), constant or sporadic and with different strengths along patient ageing [ 4 7 ]. Therefore, multiple mutational processes are operative resulting in jumbled composite signatures and tumor characteristics vary between patients of different ages [ 7 9 ]. From the Catalogue Of Somatic Mutations In Cancer (COSMIC) which includes 10,952 exomes and 1,048 whole-genomes across 40 distinct types of human cancer [ 10 ], 30 different mutational signatures were identified and publicly released ( http://cancer.sanger.ac.uk/cosmic/signatures ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in China, the estimated mortality of lung cancer is higher than the world average (2), which may be related to the neglect of early finding and diagnosis. It is reported that approximately two-thirds of patients are diagnosed at the advanced stage (3,4). During the past 5 years, a rising Chinese population, especially people in East China, is covered by medical insurance and routine physical examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Our present study found altered amino acid profiles in AML after both ATRA and valproic acid treatment, and we observed a considerable heterogeneity in pretherapy metabolite levels among AML patients when comparing (i) responders versus non-responders and (ii) non-responders with rapidly progressive disease versus other non-responders. The mechanisms behind altered amino acid profiles in cancer patients may be related to the risk of cancer [65] or reflect nutritional or microbiotic alterations, progression of the disease, cachexia or weight loss [66,67,68]. In our opinion, it is most likely that the mechanism behind the differences in amino acid metabolism between various AML patient groups is also multifactorial.…”
Section: Discussionmentioning
confidence: 99%